Perebutan Kekuasaan Internal NU - Muslimin, Imam (el Harakah: Jurnal Budaya Islam, 2004)
Since its establishment, NU has always been characterized by various internal rivalries between fractions fighting for influence. This paper discusses the internal upheaval of NU. Furthermore, the paradigmatic camps, ideological camps and competing fractions are also reviewed comprehensively. The result of competition for the power, most obviously, is the shift in power-sharing internally. At the time of its establishment until the 1950s, the greatest part of power in NU was held by non-politician kiai (syuriah) fraction, then the politician fraction (tanfidiyah) dominated it until the first half of the 1980s, and after that NU was in the hands of the fractions "Scholar". Semenjak kelahirannya, NU selalu ditandai dengan berbagai persaingan internal antar fraksi yang berebut pengaruh. Tulisan ini membahas mengenai pergolakan internal NU. Lebih jauh, kubu-kubu paradigmatik, kubu ideologis dan fraksi yang berlaga juga diulas secara komprehensif. Buah dari persaingan menuju kekuasaan itu, yang paling nyata, adalah pergeseran pembagian kekuasaan internal. Pada saat berdirinya hingga tahun 1950-an, bagian terbesar kekuasaan dalam NU dipegang oleh fraksi kiai-non politisi (syuriah), kemudian fraksi politisi (tanfidiyah) mendominasi hingga paroh pertama dekade 1980-an, dan setelah itu hingga sekarang NU berada di tangan fraksi “Cendekia”.